Progettazione sociale nei contesti di vulnerabilità. La spendibilità euristica del Project Cycle Management - Maurizio Esposito (Culture e Studi del Sociale)
Social project in contexts of vulnerability. The heuristic applicability of Project Cycle Management. the article deals with the methodology of intervention on social vulnerability through the Project Cycle Management, design technique implemented by the EU since 1993 following the Logical Framework Approach. The main purpose is to shed light on some semantic confusion regarding the issues of social planning and evaluation. Operate according to this logic means overcom-ing the fragmentation and improvisation of interventions, and thus “make” a soci-ology aimed at effectiveness of the social action and not only as a theoretical anal-ysis of self.